Pengaruh Disiplin Kerja, Komitmen, Dan Karakteristik Individu Terhadap Total Quality Management - Rismaja Putra (Pusat Riset dan Inovasi Nasional, 2022)
This research was motivated by the influence of globalization, where this has an impact on human life. This study uses the independent variable is Work Discipline (X1), commitment (X2), moderating variables, namely the individual character (X¬3), and total quality management as the dependent variable (Y). Collecting data in research using questionnaires that were distributed to 68 nurse using purposive sampling. While the analysis is performed by the data processing using SPSS version 16.0 for Windows.Results of regression analysis and t test showed that the variables of work discipline commitment variable, and variable positive effect on the individual characteristics of the variable total quality management. The coefficient of determination (R2) obtained at 0.896. This means that 89.6% of the variation can be explained by the quality of their management work discipline, commitment and individual characteristics of the remaining 10.4% of the variation is explained by other variables.